Early successful reperfusion after endovascular therapy reduces malignant middle cerebral artery infarction occurrence in young patients with large diffusion‐weighted imaging lesions. (18th June 2020) - Sabben, C.; Desilles, J. P.; Charbonneau, F.; Savatovsky, J.; Morvan, E.; Obadia, A.; Raynouard, I.; Fela, F.; Escalard, S.; Redjem, H.; Smajda, S.; Ciccio, G.; et al.
Abstract : Background and purpose: Malignant middle cerebral artery infarction (MMI) is a severe complication of acute ischaemic stroke (AIS). The aim of our study was to assess whether successful reperfusion after endovascular therapy (EVT) in AIS with clinical and imaging predictors of MMI decreased its occurrence. Methods: Data were collected between January 2014 and July 2018 in a monocentric prospective AIS registry of patients treated with EVT. Patients selected were <65 years old with severe anterior circulation AIS with a National Institutes of Health Stroke Scale score >15, baseline Diffusion‐Weighted Imaging‐Alberta Stroke Program Early Computed Tomography Score ≤ 6 and baseline diffusion‐weighted imaging lesion volume >82 mL within 6 h of symptom onset. Successful reperfusion was defined as a Thrombolysis in Cerebral Ischemia score ≥ 2b. Occurrence of MMI was the primary endpoint. Results: A total of 66 EVT‐treated patients were included in our study. MMI occurred in 27 patients (41%). In unadjusted analysis, successful reperfusion was associated with fewer MMIs (31.8% vs. 65.0%; P  = 0.015) and with more favorable outcome at 3 months (50% vs. 20%; P  = 0.023). In multivariate analysis, successful reperfusion was associated with an adjusted odds ratio (95% confidence intervals) of 0.35 (0.10–1.12) for MMI and 2.77 (0.84–10.43) for 3‐month favorable outcome occurrence. Conclusions: Early successful reperfusion performed in patients with AIS with clinical and imaging predictors of MMI was associated with decreased MMI occurrence. Reperfusion status might be considered in evaluating the need for craniectomy in patients with early predictors of MMI.